(untitled) (Revista Contexto & Saúde, 2022)
Permanent Education Strategies used in Primary Health Care Service Abstract: The Permanent Health Education (PHE) is a strategy that searches to transform the practice and organization of the work process from the demand of its own work. A exploratory, descriptive, qualitative research, case study type, that aimed to unveil the arrangements built by the health team that allowed the work management during the qualification program of the Primary Health Care. The data was collected in the period of July 2018 to April 2019 through observation-participant study tool and semi structed interviews with workers of a Family Health Care Unit in a city of Paraná. The results showed many arrangements developed by the work team: general and staff meetings, joint effort for risk stratification and setting-up groups for the users. The protagonism of the workers enabled the program to be a space for PHE. It is concluded that the seal drove the team to develop and work in cooperation. The PHE developed by the staff gave the opportunity to minimize the logics of the vertical process catch and give quality to its arrangements.